Cosmic ray–driven electron-induced reaction theory quantifies spatiotemporal variations in lower-stratospheric ozone and temperature - Qing-Bin Lu (Proceedings of the National Academy of Sciences, 2025)
Cosmic rays (CRs) play an important role in affecting planetary and interstellar climate and environment. Here, we apply the CR–driven electron-induced reaction (CRE) theory of ozone depletion to obtain a quantitative understanding of spatiotemporal variations in Earth’s lower-stratospheric ozone (LSO) and temperature, which provide fingerprints for the mechanisms of ozone depletion and examine the impact of nonhalogen greenhouse gases on the ozone layer. We first show from observations that both LSO and temperature display pronounced 11-y cyclic variations over Antarctica and mid-latitudes, while weak (no apparent) cyclic variations over the tropics. These observations are consistent with the prediction by the CRE theory. Second, our no-parameter CRE theoretical calculations give the vertical profile of ozone loss in perfect agreement with observations at the Antarctic Syowa station and reproduce well the time-series variations of both LSO and temperature in the polar, mid-latitude, and tropical regions, including the previously reported large ozone depletion in the lower stratosphere over the tropics. The results also demonstrate that both LSO and temperature are controlled by CRs and ozone-depleting substances (ODSs) only. Moreover, CRE calculations exhibit complex phenomena in future trends of LSO and temperature, which are strongly affected by the future trend of CR fluxes. The latter might even lead to almost no recovery of the ozone hole over Antarctica and no returning to the 1980 level over the tropics by 2100. This study greatly improves quantitative understanding of ozone depletion and climate in the global lower stratosphere and offers predictions on future trends.